#TITLE_ALTERNATIVE# - (NIM 20195002), Masmui
ABSTRACT: Consider the linear system (FORMULA) where x is a state vector , u is a control variable (an input). y is an output. and the elements of the matrices A, B, C, and D are assumed to be continuous functions of time defined on. In this paper we discuss uniform stability and exponential stability of the differential equation x(t) = A(t) x(t), uniform bounded input bounded output (BIBO) stability of the linear system (1), and the relation between uniform bounded input bounded output (BIBO) stability of the linear system (1) and exponential stability of the differential equation i(t) = A(t) x(t).